USING THE NINTENDO WII IN REHABILITATION THE DUCHENNE MUSCULAR DYSTROPHY. (Fiep Bulletin - online, 2014)
Introduction: Duchenne Muscular Dystrophy (DMD) is a recessive disease related to the X chromosome. The deficiency of a gene (Xp21) results in imperfection in the production of dystrophin protein. It gradually evolves to muscle weakness. Objectives: to verify the effectiveness of the use of the Nintendo Wii in the rehabilitation of Duchenne Muscular Dystrophy. Methods: A patient with DMD, male, 10 years old participated in the study. The Video Game Nintendo Wii was used for his rehabilitation. The evaluation was carried out using the GMFM (RUSSEL, 2002), EDM (ROSA NETO, 2002), neuropsychological interview and two questionnaires developed for research. Results: Using the GMFM score, it was obtained a good prognosis of 84% on pre-test and 92% on post-test. In the DMS, the best performing area on the pre-test was temporal organization and on the post-test, EDM motor skills and temporal organization; yet, the worse performance on the pre-test was spatial organization and on the post-test, body schema. Through the questionnaires' application, a high level of motivation and satisfaction of the patient was observed. Conclusion: the results showed that the use of the Nintendo Wii in the rehabilitation of the DMD increased motor skills development (temporal organization and fine motor skills) and also reinforced the patient's motivation.
Keywords: Nintendo Wii; Duchenne Muscular Dystrophy; Rehabilitation.